Preventing the Construction of Cult Behavior towards Habibs in Indonesia: Study Takhrij and Syarah Hadith - Subagja, Suni; Ramadhan, Fauzy (Journal of Takhrij Al-Hadith, 2025)
This study aims to discuss the hadith about Habib. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about Habib in Ahmad's narration No. 9902. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Ahmad No. 9902 is relevant to be used as a motivation in preventing the cult behavior of Habibs in Indonesia.